Influence of birth quarter on the rate of physical activities and sports participation - Larouche, R.; Laurencelle, L.; Grondin, S.; Trudeau, F. (Journal of Sports Sciences, 2010)
The purpose of this study was to assess the potential influence of birth quarter on the frequency of physical activity and participation in specific activities during adulthood. We used data from one national and one provincial survey, the 2005 Canadian Community Health Survey and the 1998 Quebec Social and Health Survey (Enquête sociale et de santé du Québec) respectively. We analysed the distribution of participants at each level of practice of a given leisure activity and work-related physical activity. In the Canadian Community Health Survey, a relative age effect was found for participation in soccer in the 25- to 60-year-old population. However, for volleyball, a significant relative age effect was also observed but with over-representation of the last quarters of the year for the whole population and for men aged 12-60 years. In the Quebec Social and Health Survey, significant differences in the frequency of distribution without a relative age effect were revealed for participation in women's ice hockey, work-related physical activity level, and stage of change for physical activity. Overall, the data indicate that the systematic relative age effect reported in other studies for some competitive sports, such as ice hockey and soccer, is not as prevalent in leisure physical activities during adulthood. This may reflect lower competitive selection and attrition in population physical activity compared with competitive sports in younger athletes.